Cryptotanshinone enhances wound healing in type 2 diabetes with modulatory effects on inflammation, angiogenesis and extracellular matrix remodelling. (1st January 2020) - Song, Min; Chen, Lu; Zhang, Lusha; Li, Chunxiao; Coffie, Joel Wake; Fang, Zhirui; Zhang, Liyuan; Wang, Shaoxia; Gao, Xiumei; Wang, Hong
Abstract: Context: Cryptotanshinone (CT) is a diterpene quinone compound from Salvia miltiorrhiza Bge. Labiatae has been widely used in cardio-cerebral vascular diseases, which could be potentially effective in treating diabetic wounds. Objective: This study evaluates the wound healing activity of CT by employing an excisional wound splinting model in db/db mice. Materials and methods: Wounds were induced at the dorsum of non-diabetic (db/+) and diabetic (db/db) mice and treated with sodium carboxymethyl cellulose (CMC-Na) or 300 mg/kg/d CT for 16 days. Wound closure was measured every two days. Body weight, fasting blood glucose, re-epithelialization, granulation, leukocyte infiltration, capillary density, collagen deposition and expressions of CXCL1, CXCL2, VEGF, Ang-1, p-eNOS, eNOS, α-SMA, MMP2 and MMP9 were analysed. Expression of VEGF and tube formation was measured in vitro with human umbilical vein endothelial cells (HUVECs). Results: CT significantly accelerated rate of wound closure, as the contraction ratio increased from 68% (non-treated group) to 83% (CT-treated group) at days 16 post-injury. A significant increase was observed in re-epithelialization and granulation tissue formation. Mechanistically, CT suppressed leukocyte infiltration and CXCL1 and CXCL2 expression. CT treatment also increased blood vessel density and expression level of VEGF, Ang-1 and p-eNOS. In vitro, CT boosted expression of VEGF and tube formation of endothelial cells. Moreover, extracellular matrix (ECM) remodelling was enhanced by CT via promoting fibroblast transformation and inhibiting MMP2 and MMP9. Conclusions: Our study provides evidence that CT could be developed as a potential therapeutic agent for the treatment of chronic diabetic wound healing.